PERSEPSI MASYARAKAT TENTANG KB PRIA DI KABUPATEN DEMAK (STUDI PADA MASYARAKAT PESISIR DAN MASYARAKAT KOTA DI KABUPATEN DEMAK) - Muchamad Taufik; Trixie Salawati (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background: Family planning is an attempt to regulate or control the number of births. Male participants of Family Planning in Indonesia is still low in comparison with other countries. This study aims to determine perceptions of male family planning in urban community and coastal community. Methods: This type of research is observational research using analytical survey, the independent variable is the coastal areas and urban areas and the dependent variable is the perception of KB Men. The sample used in this study is Moro Villagers and Bintoro Villagers, taken by simple random sampling technique with a number of respondents were 63 respondents. Analysis of the data using two different test mean (t-Independent). Results: Results of Independent T-test revealed that there is a difference in perception between Male Family Planning of coastal communities and urban planning communities. Urban communities have a more positive perception (65.7%) and coastal communities (64.3%). Urban communities have a positive perception about family planning slogan, number of male contraception according to BKKBN, MOP, and vasectomy is a long-term contraception, and become family planning acceptors should be decided together. Coastal communities have a negative perception about the amount of contraception by BKKBN, MOP and vasectomy is a long-term contraception and family planning only for women only. Conclusion: There is a difference in the public perception of coastal communities and cities of birth Male p=0.000.